The influence of positive affect on sensitivity to important omissions - Mantel, Susan P.; Montag-Smit, Tamara; Kardes, Frank R.; Barchetti, Alberto (Frontiers in Psychology, 2022)
It is surprisingly difficult to notice when important information is missing (omission neglect) and yet, social media, advertisements, and other forms of communication typically only include one-sided information or positive attributes and omit opposing views or negative attributes. Even though it is surprisingly difficult to overcome this natural tendency, there are circumstances when decision makers are more sensitive to omissions. Understanding how and when decision makers can overcome this omission neglect tendency can be helpful to improve decision making in many situations. This paper investigates positive affect as a potential factor that can elicit sensitivity to omissions and alert decision makers to the need for additional information when important information is, in fact, missing. Four experiments use a consumer product choice situation to show that when decision makers are making an important decision, positive affect increases the likelihood that they will report a greater desire for additional product information (experiments 3 & 4) and temper their purchase interest in the target product. These results are shown using inference (experiments 1, 2, and 3) and by explicitly comparing a product choice with full and partial information (experiment 4). The results are discussed in terms of omission neglect literature as well as implications of the results for understanding the role of positive affect in information processing, judgment, and decision-making. These findings have implications for policy makers, marketers and others who are interested in message processing.